(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
This paper presents the development of a stress detector using facial expression analysis in Python, utilizing the Deep Face library. Also, after detecting whether the person is in stress or not, it allows the user to inform about his stress to the preferred his/her family member by sending an automated WhatsApp message and showing some remedies to reduce stress.